CIMP Status of Interval Colon Cancers: Another Piece to the Puzzle - Arain, Mustafa A; Sawhney, Mandeep; Sheikh, Shehla; Anway, Ruth; Thyagarajan, Bharat; Bond, John H; Shaukat, Aasma (The American journal of gastroenterology, 2010)
Colon cancers diagnosed in the interval after a complete colonoscopy may occur due to limitations of colonoscopy or due to the development of new tumors, possibly reflecting molecular and environmental differences in tumorigenesis resulting in rapid tumor growth. In a previous study from our group, interval cancers (colon cancers diagnosed within 5 years of a complete colonoscopy) were almost four times more likely to demonstrate microsatellite instability (MSI) than non-interval cancers. In this study we extended our molecular analysis to compare the CpG island methylator phenotype (CIMP) status of interval and non-interval colorectal cancers and investigate the relationship between the CIMP and MSI pathways in the pathogenesis of interval cancers. We searched our institution's cancer registry for interval cancers, defined as colon cancers that developed within 5 years of a complete colonoscopy. These were frequency matched in a 1:2 ratio by age and sex to patients with non-interval cancers (defined as colon cancers diagnosed on a patient's first recorded colonoscopy). Archived cancer specimens for all subjects were retrieved and tested for CIMP gene markers. The MSI status of subjects identified between 1989 and 2004 was known from our previous study. Tissue specimens of newly identified cases and controls (between 2005 and 2006) were tested for MSI. There were 1,323 cases of colon cancer diagnosed over the 17-year study period, of which 63 were identified as having interval cancer and matched to 131 subjects with non-interval cancer. Study subjects were almost all Caucasian men. CIMP was present in 57% of interval cancers compared to 33% of non-interval cancers (P=0.004). As shown previously, interval cancers were more likely than non-interval cancers to occur in the proximal colon (63% vs. 39%; P=0.002), and have MSI 29% vs. 11%, P=0.004). In multivariable logistic regression model, proximal location (odds ratio (OR) 1.85; 95% confidence interval (CI) 1.01-3.8), MSI (OR 2.7; 95% CI 1.1-6.8) and CIMP (OR 2.41; 95% CI 1.2-4.9) were independently associated with interval cancers. CIMP was associated with interval cancers independent of MSI status. There was no difference in 5-year survival between the two groups. Interval cancers are more likely to arise in the proximal colon and demonstrate CIMP, which suggests there may be differences in biology between these and non-interval CRC. Additional studies are needed to determine whether interval cancers arise as a result of missed lesions or accelerated neoplastic progression.